Influence of physical crust cover on the wind erodibility of soils in the inland Pacific Northwest, USA. Issue 8 (29th March 2021) - Pi, Huawei; Webb, Nicholas P.; Huggins, David R.; Sharratt, Brenton
Abstract: Soil crusts are especially important for agricultural fields in the inland Pacific Northwest where there is a high wind erosion risk due to exposure of fine erodible soils in fallow croplands. The objective of this study was therefore to evaluate the effect of physical soil crust cover on wind erosion and identify critical soil crust cover amounts to control wind erosion. The effect of crust cover of five loessial soils on wind erosion was tested in a wind tunnel. The results indicated that crust cover appeared to have little influence on soil loss until crust cover was > 30%. Soil loss at this percentage of crust cover was 55.04% to 68.08% lower as compared with a soil surface devoid of crust cover for the five soil types. The relationship between soil loss and crust cover appeared to be nearly a linear function, although an exponential function also provided a good fit to the data. With progressive development of a crust cover, the rate of change in soil loss varied among soil types. From 0 to 100% crust cover, the rate of change in soil loss ranged from −312.8 g m −2 for Palouse silt loam to −1449.1 g m −2 for Warden sandy loam. The rate was not only associated with intrinsic soil erodibility, but also crust stability and abrasion flux. Due to the lower intrinsic soil erodibility and greater crust stability, Palouse silt loam crust was characterized by lower flaking potential and limited abrasion flux relative to the other tested soil types. The Single‐event Wind Erosion Evaluation Program (SWEEP) was used to simulate and identify the effect of crust cover on erosion processes. Differences between simulated and measured soil loss suggest that cracks in soil crusts may affect soil loss and should be incorporated into the SWEEP to expand the model capability for representing crusted soils. Abstract : Crust cover appeared to have little influence on soil loss until crust cover was > 30% for five loessial soils. The rate of change in soil loss varied among soil types, and ranged from −3.13 to −14.49 g m ‐2 per unit of percentage of crust cover.